Role of adhesion molecules in activation signaling in T lymphocytes. - Dustin, M (2001)
The T cell and antigen-presenting cell communicate to initiate an immune response through formation of an immunological synapse. This specialized cell-cell junction is compartmentalized into adhesion molecule and T cell receptor enriched regions or SMACs. Distinct signals seem to be generated in the T cell receptor and adhesion molecule-dominated regions. This review focuses on how these distinct signaling pathways may be integrated within the T cell to set thresholds for T cell activation, proliferation, and survival.